APOE genotypes and dyslipidemias in a sample of the Portuguese population - Rodrigues, M.O. (2005)
The objective of this work was to study the distribution of apolipoprotein E (APOE) genotypes in a sample of the Portuguese population, and its association with the dyslipidemias observed. Study participants were healthy users of local Public Health Laboratories in six regions of mainland Portugal (Porto, Vila Real, Viseu, Lisboa, Portalegre and Faro). A total of 779 men and 1153 women aged 15-74 years agreed to participate. Fasting lipid levels and APOE genotypes were determined centrally at the National Institute of Health in Lisboa. The frequency distribution of APOE alleles was: epsilon2=5.3%, epsilon3=84.9% and epsilon4=9.8%. Dyslipidemias were present in 66.6% of men and 60.7% of women. Comparison of APOE genotypes and relative allele frequencies showed that in dyslipidemic compared to normolipidemic subjects, the epsilon4 allele was more frequent in both sexes, although in a more pronounced way in men than in women due to higher frequencies of epsilon3/epsilon4 and epsilon4/epsilon4 genotypes. The known association of the epsilon4 allele with high cholesterol levels, the association of the epsilon2 allele with low cholesterol levels, and the association of the epsilon2 allele with high levels of triglycerides and low levels of high-density lipoprotein-cholesterol were confirmed in this study.